Adequações curriculares na área da deficiência intelectual: análise de uma realidade - Boer, Wania Aparecida (Universidade Federal de São Carlos, 2012)
The inclusion of students with intellectual disabilities in Brazilian state public education is increasing. Therefore, access, retention and learning are effective legal guarantees of the inclusive educational process. This process is not limited to the school, but the effectiveness of inclusive practices to ensure educational responses to these students for their learning and development of their autonomy. However, if the educational system does not provide significant curricular adaptations that meet the specificities of each student and a collaborative work of all school staff, that effective learning will not occur and again the student will be subject to exclusion. Considering the context mentioned, this study aims to describe and analyze a formative action to build a curriculum plan that meets all students, including those considered with intellectual disabilities. The survey was conducted in a board of education within the State of São Paulo from 2007 until 2009. Study participants were 18 teachers who comprised the study group SAPE. The study has a qualitative approach, outlined by the case study and had four spreadsheets as tools that served as the basis for the development stage of the plan curricular adjustment. This study indicates the following results: the spreadsheets worked as facilitator for the task of teaching with students with ID, as production of documents for use by staff of the Board of Special Education Board, and last but not least, as improvement of the group work promoting further studies and greater involvement of the study group during the continuous education program for other teachers. It has been also provided teachers and coordinators the possibility of adjusting curricular plans to other students who did not have disability, but learning problems.
Keywords: Educação especial; Deficiência intelectual; Inclusão escolar; Adequação Curricular; Special Education; Curricular Adjustment; Intellectual Disabilities; Inclusive School; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL